Novel PVDF-PVP hollow fiber membrane augmented with TiO2 nanoparticles: preparation, characterization and application for copper removal from leachate - Abba, Mohammed Umar; Che Man, Hasfalina; Azis, Raba'ah Syahidah; Idris, Aida Isma; Hamzah, Muhammad Hazwan; Yunos, Khairul Faezah; Katibi, Kamil Kayode (MDPI, 2021)
High proportion of copper has become a global challenge owing to its negative impact on the environment and public health complications. The present study focuses on the fabrication of a polyvinylidene fluoride (PVDF)-polyvinyl pyrrolidone (PVP) fiber membrane incorporated with varying loading (0, 0.5, 1.0, 1.5, and 2.0 wt%) of titanium dioxide (TiO2) nanoparticles via phase inversion technique to achieve hydrophilicity along with high selectivity for copper removal. The developed fibers were characterized based on scanning electron microscopy (SEM), energy dispersive X-ray spectroscopy (EDX), permeability, porosity, zeta potential, and contact angle. The improved membrane (with 1.0 wt% TiO2) concentration recorded the maximum flux (223 L/m2·h) and copper rejection (98.18%). Similarly, 1.0 wt% concentration of TiO2 nanoparticles made the membrane matrix more hydrophilic with the least contact angle of 50.01°. The maximum copper adsorption capacity of 69.68 mg/g was attained at 1.0 wt% TiO2 concentration. The experimental data of adsorption capacity were best fitted to the Freundlich isotherm model with R2 value of 0.99573. The hybrid membrane developed in this study has considerably eliminated copper from leachate and the concentration of copper in the permeate was substantially reduced to 0.044 mg/L, which is below standard discharge threshold.